2019
DOI: 10.1111/cas.14032
|View full text |Cite
|
Sign up to set email alerts
|

Association between certain non–small cell lung cancer driver mutations and predictive markers for chemotherapy or programmed death‐ligand 1 inhibition

Abstract: This study aimed to analyze the association between driver mutations and predictive markers for some anti–tumor agents in non–small cell lung cancer ( NSCLC ). A cohort of 785 Chinese patients with NSCLC who underwent resection from March 2016 to November 2017 in the First Affiliated Hospital of Guangzhou Medical University was investigated. The specimens were subjected to hybridization capture and sequence of 8 important NSCLC ‐related drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…It appeared that the molecular subtypes in our study were not related to certain gene mutations but the pattern of mutations involving multiple genes, which is quite different to the molecular alterations when the driver genes were not excluded. [ 5,20,21 ] Therefore, further investigation in this regard is warranted. Furthermore, since the molecular subtypes described were associated with survival to first‐line chemotherapy, it is possible they may similarly associate with survival to subsequent line chemotherapies (e.g., docetaxel or gemcitabine in NSCLC or topotecan in SCLC).…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that the molecular subtypes in our study were not related to certain gene mutations but the pattern of mutations involving multiple genes, which is quite different to the molecular alterations when the driver genes were not excluded. [ 5,20,21 ] Therefore, further investigation in this regard is warranted. Furthermore, since the molecular subtypes described were associated with survival to first‐line chemotherapy, it is possible they may similarly associate with survival to subsequent line chemotherapies (e.g., docetaxel or gemcitabine in NSCLC or topotecan in SCLC).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alternations were assessed by targeted next-generation sequencing (NGS) to cover critical mutations involving nine major drivers ( EGFR, ALK, RAS, ROS1, RET, BRAF, PIK3CA, MET , and HER2 ) in NSCLC. 21 In brief, DNA was extracted and quantified by using the QIAamp DNA FFPE Tissue Kit (Qiagen, Hilden, Germany) and Qubit fluorometer (Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturers’ instructions. The products were then captured and sequenced on the Ion Proton Sequencer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) such as programmed cell death‐1 (PD‐1)/programmed cell death ligand‐1 (PD‐L1) antibodies have led to unprecedented durable clinical benefit for NSCLC, but response rates are low for patients with targetable driver mutations 15 . Biomarker studies have revealed a significant correlation between PD‐L1 expression and the likelihood of a response to PD‐1 inhibitors, whereas EGFR mutation appears to be a negative predictive factor 16,17 . Given that most sensitizing EGFR mutations are not responsive to PD‐1 blockade either exon 19 deletions or L858R in exon 21; however, it is unclear whether such treatment is also without benefit in patients with uncommon EGFR mutations 18 .…”
Section: Introductionmentioning
confidence: 99%